The Translation of Oϒn in the Old Latin Gospels - Parker, David C. (New Testament studies, 1985)
This study became necessary in the course of my work on Codex Bezae. I wished to ascertain the degree of consistency with which the version used one Latin word to translate one Greek one, in order to find differences between the Mss, to assess their usefulness in supporting Greek readings, and to place the relation between the two columns of Codex Bezae in a new light. The advantages in choosing οὖν were, first its frequency, second its insignificance, with the implication that a reviser would pay little or no attention to it. The disadvantage is that it is not used uniformly, being shunned by Mark but embraced by John.